Unlocking Romania’s forest-based bioeconomy potential: knowledge-action-gaps and the way forward - Giurca, Alexandru; Nichiforel, Liviu; Stăncioiu, Petru Tudor; Drăgoi, Marian; Dima, Daniel-Paul (Land, 2022)
As national governments continue developing bioeconomy strategies, the forest-based sector becomes increasingly important. Romania’s forest sector can be at the heart of a sustainable circular-bioeconomy transition. However, despite recently launching its national forest strategy, the country has yet to produce a comprehensive bioeconomy strategy where the forest sector is properly acknowledged and integrated. Here, we discuss the potential opportunities and challenges for developing a national circular-bioeconomy strategy that builds around the forest-based sector. ...